Endoscopic Microdiscectomy Versus Conventional Discectomy for Lumber Disc Diseases; A Randomized Controlled Trial at Tertiary Care Hospital - Badar Uddin Ujjan, Shahid Nawaz, Saqib Khalil, Manqoosh ur Rehman, Amjad Maqsood, Matteo De Simone (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the efficacy of endoscopic microdisectomy versus conventional discectomy for lumber disc disease. Study Design: Randomized Control trial Place and Duration: Dow International Medical College and Hospital OJHA Campus, Karachi during the period from December, 2021 to May, 2022. Methods: Total 70 patients of both genders were presented in this study. Patients detailed demographics age, sex and BMI were recorded after taking written consent. Patients were aged between 18-70 years, Patients were divided in to two groups I and II. Group I had 35 patients and underwent for endoscopic microdisectomy and group II received conventional discectomy among 35 patients. The research included patients with low back pain radiating to the legs and prolapsed intervertebral discs at the L5–S1 and L4–L5 levels on MRI. Post-operatively effectiveness was observed between both groups, by using Oswestry disability index (ODI) in follow up of 10 months. Complete data was analyzed by SPSS. Results: Total 34 (48.6%) patients were females and 36 (51.4%) were males. Mean age of the patients were 48.32± 6.44 years with mean BMI 26.14± 3.23 kg/m2. Significantly no difference was observed between age and BMI. Patients who had prolapsed disc at L4-5 levels were 26 (37.14%) and 44 (62.86%) patients had prolapsed disc at L5-S1. Mean post-operative ODI in group I was 21.14± 54 and in group II was 24.16± 3.31. Mean post-operative vas in group I was 3.5 and in group II was 5.7. In group I hospital stay, blood loss and complications were observed less as compared to group II. Conclusion: We concluded in this that both endoscopic microdisectomy and conventional discectomy was effective and safe procedures. But conventional discectomy was found less effective as compared to endoscopic microdisectomy in terms of rapid mobilization and postoperative pain. Keywords: Oswestry Disability Index (ODI), Lumbar Disc Prolapse, Endoscopic Discectomy, Visual Analog Score (VAS)